Targeting LOX-1 Inhibits Colorectal Cancer Metastasis in an Animal Model - Murdocca, Michela; Capuano, Rosamaria; Pucci, Sabina; Cicconi, Rosella; Polidoro, Chiara; Catini, Alexandro; Martinelli, Eugenio; Paolesse, Roberto; Orlandi, Augusto; Mango, Ruggiero; Novelli, Giuseppe; Di Natale, Corrado; et al. (Frontiers in Oncology, 2019)
Recurrence and metastasis are the primary causes of mortality in patients with colorectal cancer (CRC). Effective tools to reduce morbidity and mortality of CRC patients are necessary. LOX-1, the ox-LDL receptor, is strongly involved in inflammation, obesity and atherosclerosis. Several studies assessed its role in carcinogenesis process, linking ROS, metabolic disorders and cancer. Also we have demonstrated in vitro that LOX-1 expression correlates to the aggressiveness of human colon cancer and its downregulation weakens the tumoral phenotype, indicating its potential function as a biomarker and a target in CRC therapy. Here we further investigate in vivo the role of LOX-1 in colon tumorigenesis by xenografting procedures, injecting in nude mice both subcutaneously and intravenously human high grade metastatic colorectal cancer cells, DLD-1, in which LOX-1 expression has been downregulated by shRNA (LOX-1RNAi cells). Histopathological and immunoistochemical evaluations have been performed on xenograft tumors. The experiments have been complemented by the analysis of the volatile compounds (VOCs) collected from the cages of injected mice and analysed by gas-chromatography and gas sensors. After intravenous injection of LOX-1RNAi cells, we found that LOX-1 silencing influences both the engraftment of the tumor and the metastasis development, acting by angiogenesis. For the first time we have observed that LOX-1 inhibition significantly prevents metastasis formation in injected mice and in the same time induces a downregulation of VEGF-A165, HIF-1α and -catenin, whose expression is involved in cell migration and metastasis, and a variation of histone H4 acetylation pattern, suggesting also a role of LOX-1 in regulating gene transcription. The analysis of the volatile compounds (VOCs) collected from the cages of injected mice has evidenced a specific profile in those xenograft mice in which metastasis originates. These findings underline the role of LOX-1 as a potential target for inhibition of tumor progression and metastasis, enhancing current therapeutic strategies against colorectal cancer.